Attenuation by habitual alcohol drinking of the associations of obesity with blood pressure and pulse pressure. Issue 1 (3rd November 2022) - Wakabayashi, Ichiro; Daimon, Takashi
Abstract : Background: Obesity and alcohol drinking are known to be risk factors for hypertension. However, it remains to be determined whether alcohol affects the relationships of obesity with blood pressure and pulse pressure. Methods: The participants in this study were 29 171 men who had received annual health checkups. Relationships of BMI with blood pressure and pulse pressure were investigated in four subject groups divided by average daily alcohol consumption (grams of ethanol/day), non-, light (<22), moderate (≥22 and <44) and heavy (≥44) drinkers. Results: BMI was significantly correlated with SBP and DBP levels both in nondrinkers and drinkers. The strength of the correlations was significantly weaker in drinkers than in nondrinkers. Odds ratios for hypertension in subjects with vs. subjects without obesity tended to be lower with an increase in alcohol intake (odds ratios with 95% confidence intervals: 4.09 (3.69–4.52) in nondrinkers; 3.11 (2.62–3.68) in light drinkers; 2.87 (2.61–3.16) in moderate drinkers; 2.81 (2.49–3.18) in heavy drinkers). Pulse pressure was weakly but significantly associated with BMI and obesity, and these associations were significantly weaker in heavy drinkers than in nondrinkers. There were significant odds ratios for hypertension and high pulse pressure of the interaction term between obesity and alcohol drinking. Conclusion: The associations of BMI with blood pressure and pulse pressure and the associations of obesity with hypertension and high pulse pressure were weaker in drinkers than in nondrinkers. Thus, alcohol drinking attenuates the associations of obesity with hypertension and high pulse pressure.